Clinical neurology of aging - Martin L. Albert (Oxford University Press, 2000)
This thorough revision of a well-established text presents essential information on the neurobiology of aging. There are new chapters on competency and ethics, problems of daily living, psychopharmacology, and stability and falls. Written in a accessible style, this book will be invaluable to clinicians and neurologists who treat elderly patients